PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT TANAOBA LAIS MANEKAT KOTA KUPANG - Gloryna Y Klau; Struce Andriyani; Frans Gana (Universitas Nusa Cendana, 2020)
The research was conducted at PT. BPR TLM Kupang City with the object of research are employeesof PT. BPR TLM Kupang City. The problem in this research is how the transformasional leadershipstyle, motivation and employee performance of PT. BPR TLM Kupang City, whether there is aninfluence of transformational leadership style and motivation on employee performance of PT. BPRTLM Kupang City. This research is an associative research which provides an explanation of thecausal relationship between variables based on two types of data. The results showed thattransformational leadership style and motivation has a positive and significant effect on employeeperformance PT. BPR TLM Kupang City. Thus the company must continue to improve and payattention to the transformational leadership style and motivation in the company so that employeesare always competent and disciplined at work ultimately employees can provide their best abilities toachieve company goals. Keywords: Transformational Leadership Style, Motivation, Employee Performance